Fractured Foundations: Colonial Legacies, Genocidal Disruption, and Rwanda’s Economic Rebuilding - Arshiya Manchanda (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The Genocide in Rwanda Against the Tutsi, was an ethnic cleansing which took place during the Rwandan Civil war between the 7th of April 1994 to 15th of July 1994. Within these (approximately) one hundred days of bloodshed and violence, nearly a million Tutsis and their Hutu sympathisers were killed. The cause of the genocide was rooted in long term seething tensions between the Hutus and Tutsis, which were a product of Belgian Colonialism. In 1897, Germany became the first European Nation to colonise Rwanda, Belgium soon followed suit and took over during the First World War, in 1916. As Belgian colonialism took hold over the small country, so did their ideologies, and soon followed ruthless expropriation. When the colonists arrived, they accentuated the differences between the two groups by favouring the Tutsis. Historically, Hutus and Tutsis are different ethnic groups, but they do have numerous similarities; they speak the same language, have similar traditions and live in common areas. They lived in harmony 600 years ago, when Tutsis, warrior people from Ethiopia descended south and albeit few, managed to conquer Hutus inhabiting regions in Central Africa. They were promised crops in return for protection and lived in mutually acceptable harmony for centuries. On occasion, theyeven partook in intermarriage between the two. However, as effects of colonialism became more pronounced, the exacerbated seething tensions between the two groups resulted in a hundred day long genocide following the assassination of the president of Rwanda and Burundi respectively. This massacre was responsible for the murder and mutilation of an estimated 800,000 men, women and children in 1994. Rwanda’s economic struggles did not begin with the 1994 Genocide against the Tutsi, they were deeply rooted in a long history of colonial exploitation and structural inequality. Under German and later Belgian colonial rule, Rwanda’s economy was restructured to serve the interests of the colonizers, prioritizing cash crops like coffee and tea over diversified development. This laid the groundwork for dependency, poor infrastructure, and limited industrialization. Post-independence, political instability and ethnic tensions further hindered economic progress. Though the country managed a modest average annual growth rate of approximately 2.5% between 1980 and 1990, this fragile progress was entirely derailed by the genocide. The violence led to the complete unravelling of Rwanda’s socio-political fabric and pushed the economy into severe recession and hyperinflation. The destruction of infrastructure, loss of human capital, disrupted supply chains, and widespread poverty and famine caused long-lasting, perhaps irreparable, economic damage. In the aftermath, the Rwandan government has spent the past two decades implementing substantial restoration efforts aimed at rebuilding the socio-economic foundation of the country. The scale and depth of the economic devastation continue to shape the country’s recovery trajectory even today. This paper aims to analyze the long term and short term impact of the 1994 Genocide in Rwanda against the Tutsi on the economy of Rwanda and explore how the genocide was not only a result of political instability, but consistent economic deprivation at the hands of their colonizers. Even though the colonization sowed the seeds of industrialization, the genocide outbreak devastated the economy.. By applying economic principles and concepts, this paper will analyze the various factors that affected Rwanda’s economy pre, during and post the genocide, leading to the eventual implementation of restoration policies which aimed to recover Rwanda’s economy. Moreover, this paper will use Rwanda as an example to evidence that political and sociological disruptions put a break on economies that are inherently fragile.